The microbiology of rebuilding soils with water treatment residual co‐amendments: Risks and benefits. Issue 6 (25th September 2021) - Stone, Wendy; Lukashe, Noxolo S.; Blake, Lynsay I.; Gwandu, Tariro; Hardie, Ailsa G.; Quinton, John; Johnson, Karen; Clarke, Catherine Elaine
Abstract: Water treatment residual (WTR) is composed of sludges from the potable water treatment process, currently largely destined for landfill. This waste can be diverted to rebuild degraded soils, aligning with the UN's Sustainable Development Goals 12 (Consumption and Production) and 15 (Terrestrial Ecosystems). Biosolids are tested against stringent pathogen guidelines, yet few studies have explored the microbial risk of WTR land application, despite anthropogenic impacts on water treatment. We explored the microbial risks and benefits of amending nutrient‐poor sandy soil with WTRs. Our results showed that the culturable pathogen load of wet and dry WTRs did not warrant pre‐processing before land application, according to South African national quality guidelines, with fecal coliforms not exceeding 10 4 colony forming units per gram dry weight in wet sludges sampled from four South African and Zimbabwean water treatment plants and decreasing upon drying and processing. There was no culturable pathogenic (fecal coliforms, enterococci, Salmonella, and Shigella ) regrowth in soil incubations amended with dry WTR. However, the competition (microbial load and diversity) introduced by a WTR co‐amendment did not limit pathogen survival in soils amended with biosolids. Application of WTR to nutrient‐poor sandy soils for wheat ( Triticum aestivum L.) growth improved the prokaryotic and eukaryotic culturable cell concentrations, similar to compost. However, the compost microbiome more significantly affected the bacterial beta diversity of the receiving soil than WTR when analyzed with automated ribosomal intergenic spacer analysis. Thus, although there was a low pathogen risk for WTR amendment in receiving soils and total soil microbial loads were increased, microbial diversity was more significantly enhanced by compost than WTR. Core Ideas: Microbial risks and benefits of water treatment residual (WTR) land application were explored to inform SDG12 and SDG15. Pathogen concentrations in WTR did not require pre‐processing for land application. No pathogen regrowth was evident in nutrient‐poor sandy soils incubated with WTR. Microbial competition in WTR, did not limit biosolid pathogen persistence. Both WTRs and, more so, compost co‐amendments increased soil microbial load and diversity.